Measuring Wellbeing in the SOEP - Ulrich Schimmack (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
I define wellbeing as preference realization. Wellbeing can be measured with affective (the amount of pleasant versus unpleasant experiences) and cognitive (satisfaction with life in general and life domains) measures. Since its inception 25 years ago, the SOEP has included cognitive measures of wellbeing. In 2007, the SOEP included four items (happy, sad, angry, afraid) as an affective measure of wellbeing. This paper examines similarities and differences between cognitive and affective measures of wellbeing. In the end, I propose a wellbeing index that combines information from measures of life satisfaction, average domain satisfaction, and affect balance.
Keywords: I31; 330; General welfare; quality of life; happiness; wellbeing